Meningkatkan Growth Mindset Melalui Layanan Konseling Kelompok Untuk Mengurangi Prokrastinasi Akademik Siswa Kelas VIIIC SMPN 1 Sikur - Yulianti, Dewi; Takiuddin, Muhamad; Ukhro, Wahyu Rabiatul (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
This research aims to improve growth mindset with group counseling services to reduce students' academic procrastination. This type of research is pre-experimental with a one group pretest posttest research design. This research methodology uses quantitative methods.The results obtained were 6.45 > 2.365, which means that there is an effect of increasing the growth mindset with group counseling services to reduce academic procrastination for class VIIIC students at SMP NEGERI 1 SIKUR. so it can be concluded that "If group counseling services are provided by increasing the growth mindset, it can reduce the academic procrastination of class VIIIC students at SMPN 1 SIKUR"